2020
DOI: 10.1177/0954410020972581
|View full text |Cite
|
Sign up to set email alerts
|

Multi-physics simulation of an insect with flapping wings

Abstract: In this paper, the unsteady aerodynamic of an insect’s forward flight has been carried out with a novel approach. In order to fully utilize the available powerful solvers, an innovative intermediary MATLAB code has been written for the high-fidelity time-resolved multi-physics problems involving fluid flow and multi-body simulations. For simulating the insect’s flight, the FLUENT solver has been utilized to determine aerodynamic forces and moments of the wings and main body while ADAMS software has been employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…It is observed that the average deviation of our data with other works is less than 6%. Validation of computational studies have been done in several previous works [45][46][47][48][49][50][51][52][53][54][55] Figure 4 displays the flow stream and concentration of the coolant gas (He and CO 2 ) for injection system released from the tip of disk located on the spike. As expected, the formation of the circulations in the cavity is main flow physic of the proposed configurations.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the average deviation of our data with other works is less than 6%. Validation of computational studies have been done in several previous works [45][46][47][48][49][50][51][52][53][54][55] Figure 4 displays the flow stream and concentration of the coolant gas (He and CO 2 ) for injection system released from the tip of disk located on the spike. As expected, the formation of the circulations in the cavity is main flow physic of the proposed configurations.…”
Section: Resultsmentioning
confidence: 99%
“…This study tries to visualize the impacts of the non-uniform source of magnetic field on the heat transfer performance of shell and tube heat exchangers. Although this type of heat exchanger is the most convenient one and has been widely investigated [31][32][33][34][35] , the performance of this type under the impact of the non-homogenous magnetic field was not fully discussed.…”
Section: Influence Of Non-uniform Magnetic Field On the Thermal Effic...mentioning
confidence: 99%
“…where n is the number of assumed modes. It should be noted that, even though, substitution of equation (11) in equation (10) results in a nonlinear displacement equation in terms of generalized coordinates, the nonlinear terms are only responsible for implicit condensation of the membrane modes and do not cover nonlinear effects in large amplitude deformations. The mentioned claim is based on the utilized assumption that T m contains the eigenvectors of membrane modes.…”
Section: Mwmentioning
confidence: 99%
“…1 Due to importance and inherent complexities associated with FAVs, there are some researches focused on its aerodynamic aspects. [2][3][4][5][6][7][8][9][10][11][12] On the other hand, flexibility is another significant issue with FAVs that can [13][14][15][16][17][18] potentially affect their aerodynamic loadings for sustained flights.…”
Section: Introductionmentioning
confidence: 99%